2016
DOI: 10.1080/13557858.2016.1244624
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and gender on the prevalence of insomnia in a sample of the Saudi population

Abstract: Insomnia is most prevalent among Saudi females and the elderly Saudi population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 30 publications
2
29
1
1
Order By: Relevance
“…Th e insomnia rate was also greater than that reported in another study of Saudi healthcare workers at the National Guard Hospitals in Jeddah and Riyadh, which found that 52% of women and 35% of men had inadequate sleep quality/insomnia, compared to 63% of men and 82% of women in this study [21] . However, the prevalence in this study was closer to the 78% found in a study conducted in 2016 to measure the frequency of sleep apnea among the general population [22] .…”
Section: Discussionsupporting
confidence: 67%
“…Th e insomnia rate was also greater than that reported in another study of Saudi healthcare workers at the National Guard Hospitals in Jeddah and Riyadh, which found that 52% of women and 35% of men had inadequate sleep quality/insomnia, compared to 63% of men and 82% of women in this study [21] . However, the prevalence in this study was closer to the 78% found in a study conducted in 2016 to measure the frequency of sleep apnea among the general population [22] .…”
Section: Discussionsupporting
confidence: 67%
“…Surveys of parents show that the prevalence of sleep problems in ASD is 50%–80% compared to 9%–50% in age-matched typically developing children [7,8,9,10,11,12,13,14]. Recent results showing abnormal melatonin secretion in ASD children may change the initial disregard of these disorders and suggest a possible key role of the clock and circadian regulations in ASD.…”
Section: Relationships Between Circadian Rhythms and Psychiatric Dmentioning
confidence: 99%
“…In autism, a prevalence of insomnia from 50% to 80% has been reported [3,4,5,6] compared to 9–50% in age-matched typically developing children [7,8,9,10,11]. However, the interpretation of these results has to take into consideration the high prevalence of insomnia (30%) in typically developing individuals [12,13,14]. It is noteworthy that sleep disorders are not specific to autism spectrum disorder (ASD) given that they are observed in ASD individuals with intellectual disability (ID), ID individuals without ASD, and individuals with brain injury as well as ID, suggesting a possible overlap between ASD and ID.…”
Section: Introduction: Circadian Rhythms and Their Molecular Mechamentioning
confidence: 99%
“…Older age was reported to be associated with higher frequency of insomnia. In a study, 2095 participants aged ≥18 years (range: 18-100) were evaluated and a statistically strong association between age and insomnia (p=0.001) was detected (30). In another study, data were extracted from a wide group (n=1423) of old participants (aged ≥60 years, age was found to be related with worse sleep complaints.…”
Section: Discussionmentioning
confidence: 99%